The Correlation Between Students’ Silent Reading Technique Habits and Their Reading Comprehension - Indrawan, Raihan Khairunisa; Syahfutra, Wandi; Pahmi, Pahmi (Universitas Lancang Kuning, 2025)
Reading comprehension is reading for understanding. It needs the reader to comprehend the content being read. Students have difficulty understanding the meaning of the reading text and difficulty concentrating if they read the text aloud. Students also have low reading comprehension. The research objective of the research was to determine whether the students’ silent reading technique habits have a correlation with students’ reading comprehension at the tenth-grade students of SMA Negeri 1 Pekanbaru. This research was used quantitative correlational research. The sample of this research is 105 students consisting of 3 classes. The researcher conducted a questionnaire to measure students' silent reading technique habits and to measure students’ reading comprehension, the researcher used a reading test. It could be seen from the data that the questionnaire and reading test were normally distributed with a Monte Carlo significance result of 0.067. Additionally, the correlation between silent reading technique habits and their reading comprehension was linear, proven by the linearity test score is 0.414. Based on the result of the Pearson product-moment through the SPSS 25 version, it could be seen the significance score for both variables was 0.667 which is greater than 0.05. It means the null hypothesis is accepted. In addition, it showed that there is no correlation with the ‘Very Low’ level of correlation because the Pearson correlation for the instruments score were -0.043. It may be stated that students' silent reading technique habits and reading comprehension do not correlate to a low level and a negative relationship.